Effect of Enriched Feed by n-3 fatty acids and 2% of n-6 fatty acid on Danio rerio Reproduction - Utomo, N.B.P; Nurmalia, L.; Mokoginta, I. (Jurnal Akuakultur Indonesia, 2005)
This experiment was conducted to determine the optimum n-3 fatty acid level in the diet containing 2 % of n-6 fatty acid on the reproductive performance of zebra fish (Danio rerio). There experimental diets containing 0.0; 1.0; 1.5 % n-3 fatty acid with 2.0 % n-6 fatty acid was fed to the fish, three times daily, at satiation, for two months. In order to evaluate the gonadal development of the broodstock, two gonads og fish was used for histologis preparation in every 7 days. At the end of the second month, reproductive performance was evaluated through parameters of gonad somato indeks, fecundity, fertilization rate, hatching rate, yolk egg absorbtion rate, survival rate of 3 days old larvae. Sample of fish also was taken for proximate composition as the end of this experiment. Results shows that at the fifth weeks of this experiment, gonad of fish fed on 1.0 % of n-3 fatty acid and 2.0 % n-6 fatty acid already produce eggs with the some size, while others. Still produce small size of eggs. It was found also that the whole body of fish fed an diet with 1.0% n-3 fatty acid contain the highest protein level compare to two other diets. Based on the evaluation of reproduction performance parameters, it was concluded that the optimum dietary level of n-3 fatty acid with 2.0 % n-6 fatty acid for Danio rerio was 0.81 - 0.90 %. Keywords: essential fatty, acids, reproduction, zebra fish, Danio rerio   ABSTRAK Penelitian ini bertujuan untuk menentukan kadar asam lemak n-3 optimum dalam pakan yang mempunyai kadar asam lemak n-6 tetap. Tiga macam pakan dengan kadar asam lemak n-3 berbeda yaitu 0.0; 1.0; dan 2.0 % diberikan pada ikan dengan bobot rata-rata 0.12 g. Pakan diberikan secara at satiation, 4 kali sehari selama 60 hari. Setiap 7 hari sekali diambil sampel ikan untuk pembentukan preparat histologi gonad dengan tujuan untuk mengevaluasi perkembangan gonad. Pada akhir penelitian, induk dipijahkan dan dievaluasi performan reproduksi berdasarkan parameter. Gonad Somato Indeks, fekunditas, derajat pembuahan, derajat penetasan dan kelangsungan hidup larva berumur 3 hari. Sampel tubuh ikan diakhir penelitian juga dievaluasi komposisi proksimatnya. Hasil penelitian ini memperlihatkan bahwa pada minggu ke-5 setelah pemberian pakan, gonad dari ikan yang diberi pakan asam lemak n-3 1.0 % mengandung telur-telur dengan ukuran yang seragam sedangkan ukuran telur ke dua perlakuan lainnya masih bervariasi. Kadar protein tertinggi juga terdapat pada tubuh ikan yang diberi pakan 1.0 % asam lemak n-3. Berdasarkan parameter performan reproduksi secara keseluruhan dapat disimpulkan bahwa kadar asam lemak n-3 optimum dalam pakan ikan zebra, Danio rerio adalah 0.81 - 0.90 %. Kata kunci: asam lemak, reproduksi, ikan zebra, Danio  rerio